Islamic financial consultants among young graduates: are they ready? - Abdullah, Azwan; Muhammad, Mohd Zulkifli; Mohd Rohizad, Nur Syazana; Shuib, Nur Syafiqah; Sariman, Nurazlifahayati; Md Yusof, Nur Syazwani (Universiti Teknologi MARA, Kelantan, 2018)
Islamic Financial Consultant in Takaful is one of the parts in Islamic and Finance sectors. Islamic bank in Takaful industry has to enter into high competition with other insurance plans as to be number one in this sector. Therefore, the purpose of this research is to examine the Islamic Financial Consultant; the prospect and challenges among the fresh graduate in Malaysia. Besides, this study also piloted to identify the pull factors that influence young graduate to involve in Islamic Financial Consultant in Takaful as to explore opportunities, threat and understand prospect and challenges faced by Islamic Financial Consultant in Takaful. Moreover, a total of 9 informants which consist of 4 fresh graduate, 2 academician and 3 industry players who involved in Islamic Financial Consultant in Takaful industry also are selected for the purpose of this study. For the analysis, qualitative research was used to analyse the outcome and the underpinning theory in order to ensure the research objective be achieved.